Impact of a Motivational Intervention and Interactive Feedback on Electricity and Water Consumption: A Smart Housing Field Experiment. Issue 6 (July 2020) - Legault, Lisa; Bird, Stephen; Powers, Susan E.; Sherman, Amanda; Schay, Alan; Hou, Daqing; Janoyan, Kerop
Many interventions designed to curb energy use are ineffective because they fail to inspire individuals to engage in proenvironmental behavior and interact meaningfully with energy information. This field experiment targeted individuals' personal motivations and goals in combination with sensor-recorded energy feedback to decrease electricity and water consumption. Residents from 77 "smart" apartments were randomly assigned to attend a multifaceted motivational program and set action-oriented energy goals. Participants were also randomly assigned to receive interactive energy feedback. Continuous electricity and water data were then collected for 3 months. Those who received the motivational intervention used significantly less hot water than those who did not receive the intervention. Moreover, those exposed to action-focused feedback used significantly less electricity than those who did not receive the feedback—an effect that was more pronounced in the motivation condition. Results support the use of interventions directed at personal proenvironmental motivations and action-focused group goals.